Polypharmacy: the whys, the so whats and the what nexts. (2nd May 2020) - Bennett, Frances; Sofat, Reecha
Abstract : There is an increasing awareness that polypharmacy – the use of multiple medicines by one individual – may bring harm as well as benefit. This has been termed 'problematic polypharmacy' and is associated with increased risk of admission to hospital, decreased quality of life and psychological harm. This article addresses the factors that may be contributing to the global rise of polypharmacy (the whys), the problems it can cause (the so whats), and some opportunities and strategies for improving and avoiding problematic polypharmacy in the future (the what nexts).